2021
DOI: 10.1128/msphere.00725-21
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Multidrug-Resistant Acinetobacter baumannii from a Pediatric Cancer Hospital in Egypt

Abstract: Acinetobacter baumannii represents a major health threat, in particular among immunocompromised cancer patients. The rise in carbapenem-resistant A. baumannii , and the development of resistance to the last-resort antimicrobial agent colistin, complicates the management of A. baumannii outbreaks and increases mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 105 publications
9
17
1
Order By: Relevance
“…In agreement with other studies (Al- Hassan et al, 2019;Fam et al, 2020;Wasfi et al, 2021), MLST analysis revealed the predominance of GC2 isolates in our collection (38.8%). Nevertheless, GC1 strains outweighed those that belonged to GC2 studied by others in our region (Ghaith et al, 2017;Jalal et al, 2021). Less representation (16.6%) was noted for the recently described GC9 (Müller et al, 2019) known to be endemic in Middle East countries (Al-Hassan et al, 2013, 2021Bonnin et al, 2013;Ghaith et al, 2017;Jaidane et al, 2018;Salloum et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In agreement with other studies (Al- Hassan et al, 2019;Fam et al, 2020;Wasfi et al, 2021), MLST analysis revealed the predominance of GC2 isolates in our collection (38.8%). Nevertheless, GC1 strains outweighed those that belonged to GC2 studied by others in our region (Ghaith et al, 2017;Jalal et al, 2021). Less representation (16.6%) was noted for the recently described GC9 (Müller et al, 2019) known to be endemic in Middle East countries (Al-Hassan et al, 2013, 2021Bonnin et al, 2013;Ghaith et al, 2017;Jaidane et al, 2018;Salloum et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
“…These included the novel clonal complex CC2329 Oxf (CC113 Pas ) represented by M03 (ST113 Pas / 2246 Oxf ) and M14 (ST113 Pas / ST2329 Oxf ). Isolates that belong to this CC were reported from Egypt (Jalal et al, 2021), Saudi Arabia (Lopes et al, 2015), and Brazil (Leal et al, 2020). Another ST identified here, ST164 Pas /1418 Oxf , was reported in the isolates from Myanmar (Tada et al, 2020), Vietnam (Wareth et al, 2021), Brazil (Coelho-Souza et al, 2013, Kenya (Musila et al, 2021), and as a major clone in Thailand (Khuntayaporn et al, 2021).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Accordingly, the higher biofilm-forming ability of strain #36 in comparison with strain #150 could be explained by the absence of a conserved Bap protein in this strain; vice versa, the presence of Omp33–36 could account for the enhanced adhesion to pulmonary cells of strain #150 with respect to strain #36 [ 13 ]. Accordingly, previous studies revealed the absence of the bap gene in a number of A. baumannii isolates that displayed a reduced biofilm-forming ability [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in whole-genome sequencing technology have facilitated bacterial whole-genome characterization, enhancing the ability to elucidate the antibiotic-resistant mechanism and pathogenesis in Acinetobacter baumannii [ 33 , 34 ]. However, data concerning genome analysis on colistin resistance of Acinetobacter baumannii isolated from Thailand is currently limited in the literature [ 35 ].…”
Section: Introductionmentioning
confidence: 99%